A dioctyl phthalate electrolyte for aqueous zinc ion batteries and a preparation method and application thereof
Patent Information
- Application Number
- CN202311492226.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-11-10
AI Technical Summary
然而对于锌/二氧化锰电池来说,现在还未存在一种合适的电解质
[0022]本发明提供了一种生产方便、价格适宜的电解质添加剂,通过原位形成正极CEI保护膜,对二氧化锰正极进行保护,实现锌/二氧化锰电池长循环性能的提升,最优实施例70圈循环后可达到87%的容量保持率(容量保持率=第70圈容量/70圈循环内的最高容量)。在循环过程中也是CEI膜的持续形成过程。
Smart Images

Figure CN117293414B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, specifically to the field of aqueous zinc-ion battery technology, and particularly to a dioctyl phthalate electrolyte for aqueous zinc-ion batteries, its preparation method, and its application. Background Technology
[0002] In recent years, the continued growth in the market penetration of renewable energy has increased the demand for inexpensive, safe, and durable electrochemical energy storage technologies. However, lithium-ion batteries, due to the increasing scarcity of lithium resources, high costs, and safety concerns, have not yet been widely adopted in the energy storage field. Therefore, the diversified development of new rechargeable batteries has become a priority. Among these, aqueous zinc-ion batteries, due to the abundance of zinc resources and the inherent safety of aqueous electrolytes, offer a low-cost, high-safety option for future energy storage and represent one of the development directions for energy storage systems.
[0003] Manganese dioxide's high theoretical capacity and low cost have made it widely used as a cathode material in aqueous zinc-ion batteries. However, the manganese dissolution and byproduct generation during charging and discharging can cause irreversible capacity decay in zinc / manganese dioxide batteries. Therefore, optimizing the manganese dioxide cathode is necessary and urgent for the practical application of zinc / manganese dioxide batteries.
[0004] Tianjin University disclosed an interfacial phase and its preparation method for a manganese dioxide electrode in an aqueous zinc battery in CN115911248A. The method uses a manganese dioxide electrode as the working electrode, an ammonium dihydrogen phosphate aqueous solution as the electrolyte, and a counter electrode and a reference electrode to form a three-electrode system. Cyclic voltammetry is used to react the electrode, generating a manganese phosphate nanolayer in situ on the surface of the manganese dioxide electrode, followed by drying in an oven. The electrochemically treated electrode is used as the positive electrode, zinc foil as the negative electrode, and zinc sulfate containing manganese sulfate additive as the electrolyte to assemble a battery. After cycling the battery a certain number of times, the manganese phosphate nanolayer at the manganese dioxide electrode interface transforms into a δ8MnO2 nanolayer containing a large amount of interlayer water, which can significantly enhance the H2O performance. + This invention enables rapid carrier dynamics in the battery by utilizing the storage capacity of the δ8MnO2 nanolayer interface phase. It is low-cost and simple to manufacture, and the resulting δ8MnO2 nanolayer interface phase imparts excellent rate performance and cycle stability to the manganese dioxide electrode, showing promising application prospects.
[0005] The Institute of Process Engineering, Chinese Academy of Sciences, disclosed a high-voltage resistant lithium-ion battery electrolyte and a lithium-ion battery using this electrolyte in CN114914540A. The electrolyte not only contains an oxidation-resistant co-solvent, which significantly improves the redox stability of the electrolyte, but also contains functional additives that effectively construct a stable CEI film, preventing side reactions during cycling. Due to the synergistic effect of the two components in the electrolyte, it exhibits good cycle stability in high-voltage ternary battery systems.
[0006] It is evident that choosing a suitable electrolyte has a significant impact on ion batteries. However, for zinc / manganese dioxide batteries, there is currently no suitable electrolyte.
[0007] To address the aforementioned issues, this invention has discovered that the introduction of certain electrolyte additives can form a solid interfacial film (CEI) in situ at the manganese dioxide cathode / electrolyte interface. This film plays a stabilizing role in preventing manganese dissolution and inhibiting the formation of byproducts, thereby improving cycle stability and capacity retention, and ultimately effectively enhancing the performance of zinc / manganese dioxide batteries. Summary of the Invention
[0008] The purpose of this invention is to provide an electrolyte additive that is easy to produce and reasonably priced. By forming an in-situ CEI protective film on the positive electrode, it protects the manganese dioxide positive electrode, thereby improving the long-cycle performance of zinc / manganese dioxide batteries and promoting their application in energy storage. To achieve the above objective, the electrolyte additive provided by this invention is dioctyl phthalate (DOP), and this electrolyte is named dioctyl phthalate electrolyte, or simply DOP electrolyte.
[0009] The first aspect of the present invention is to provide a dioctyl phthalate electrolyte for an aqueous zinc-ion battery, wherein the electrolyte is composed of a mixed aqueous solution of zinc sulfate and manganese sulfate and dioctyl phthalate, wherein the concentrations of each component in the mixed aqueous solution of zinc sulfate and manganese sulfate are: zinc sulfate 0.5-3 mol / L, manganese sulfate 0.01-1 mol / L, and the volume ratio of dioctyl phthalate to the mixed aqueous solution of zinc sulfate and manganese sulfate is 1 / 2-1 / 5.
[0010] Furthermore, the preferred concentrations of each component in the mixed aqueous solution of zinc sulfate and manganese sulfate are: 2 mol / L for zinc sulfate and 0.2 mol / L for manganese sulfate.
[0011] Furthermore, the preferred volume ratio of dioctyl phthalate to the mixed aqueous solution of zinc sulfate and manganese sulfate is 1 / 3.
[0012] A second aspect of the present invention is to provide a method for preparing dioctyl phthalate electrolyte for aqueous zinc-ion batteries, the specific preparation method comprising the following steps:
[0013] 1) Deionized water is added to a mixture of zinc sulfate and manganese sulfate to obtain solution A;
[0014] 2) After stirring and dispersing solution A and ultrasonicating it to obtain a homogeneous and clear solution B, i.e., the precursor solution;
[0015] 3) Add dioctyl phthalate to solution B, stir and disperse, and sonicate to obtain a homogeneous and clear solution C. Solution C is the dioctyl phthalate electrolyte.
[0016] Furthermore, the stirring time in steps 2) and 3) is 1 hour or more, the ultrasonic time is 0.3 hours or more, and the operating temperature is 25℃~35℃.
[0017] A third aspect of the present invention is to provide the application of dioctyl phthalate electrolyte for aqueous zinc-ion batteries in aqueous zinc-ion batteries.
[0018] Furthermore, dioctyl phthalate electrolyte was added to a glass fiber separator, and combined with a zinc negative electrode, a manganese dioxide positive electrode, a heat shrink film, and an aluminum-plastic film to prepare a soft-pack battery.
[0019] A fourth aspect of the present invention is to provide a pouch cell obtained by applying the aforementioned dioctyl phthalate electrolyte for aqueous zinc-ion batteries in aqueous zinc-ion batteries.
[0020] The fifth aspect of the present invention is to provide an application of the aforementioned pouch cell in the field of photovoltaic energy storage.
[0021] Compared with existing technologies, the beneficial effects are:
[0022] This invention provides an electrolyte additive that is easy to produce and reasonably priced. It protects the manganese dioxide cathode by forming an in-situ CEI protective film, thereby improving the long-cycle performance of zinc / manganese dioxide batteries. In the optimal embodiment, 87% capacity retention is achieved after 70 cycles (capacity retention = capacity at 70th cycle / highest capacity within 70 cycles). The CEI film is also continuously formed during the cycling process.
[0023] The pouch cell in this invention can meet the discharge test requirements of photovoltaic energy storage under different current densities and can meet the long-term energy storage stability requirements, thereby promoting the application of energy storage.
[0024] The electrolyte in this invention consists of a mixed aqueous solution of zinc sulfate and manganese sulfate, and dioctyl phthalate (DOP). DOP exhibits superior performance compared to other esters. Without DOP, no CEI forms on the surface of manganese dioxide. Furthermore, the zinc sulfate, manganese sulfate, and DOP components exhibit a synergistic effect; their concentrations must be within a reasonable range. High DOP concentrations prevent normal charge-discharge processes (essentially resulting in an open circuit), while low DOP concentrations, although having some effect, are ineffective. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a schematic diagram of an assembly using a DOP electrolyte pouch cell.
[0027] Figure 2 This is a comparison graph of the cycle performance of Example 1 and Comparative Example 1;
[0028] Figure 3 This is a time-voltage / current graph for Example 1;
[0029] Figure 4 Infrared image of manganese dioxide cathode sheet in Example 1;
[0030] Figure 5 This is a cyclic performance graph for Example 2;
[0031] Figure 6 This is a cyclic performance diagram for Example 3;
[0032] Figure 7 This is a cyclic performance diagram for Example 4;
[0033] Figure 8 Discharge diagrams at different current densities for Example 5;
[0034] Figure 9 This is a diagram showing the photovoltaic energy storage cycle performance of Example 6;
[0035] Figure 10 This is a time-voltage / current plot for Comparative Example 2;
[0036] Figure 11 The time-voltage / current plot is shown in Comparative Example 3;
[0037] Figure 12This is a time-voltage / current plot for Comparative Example 4;
[0038] Figure 13 This is a comparison graph of the electrochemical impedance spectroscopy of Example 1 and Comparative Example 4;
[0039] Figure 14 This is a charge-discharge cycle diagram for Comparative Example 5;
[0040] Figure 15 This is a charge-discharge cycle diagram for Comparative Example 6. Detailed Implementation
[0041] To enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention, and to make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be further described below.
[0042] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0043] Example 1
[0044] 1) Preparation of the electrolyte in Example 1 (volume ratio of DOP:precursor solution = 1 / 3): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 16.7 mL of dioctyl phthalate was added to solution B, stirred for 1 hour, and sonicated for 0.3 hours to obtain the DOP electrolyte.
[0045] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0046] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 24) Preparation of the soft-pack battery: The DOP electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are combined. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, the separator (with DOP electrolyte added), and the zinc negative electrode in that order, then placing them in a heat-shrink film and heating it to ensure that the heat-shrink film adheres tightly to and fixes the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery.
[0047] 5) Testing of pouch batteries: Using the Blue Electric system, at 10mA / cm 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 2 Example 1 and Appendix Figure 3 As shown, an 87% capacity retention rate can be achieved after 70 cycles (capacity retention rate = capacity at 70th cycle / maximum capacity within 70 cycles).
[0048] 6) Positive electrode characterization: Infrared characterization was performed on manganese dioxide positive electrodes with different cycling cycles to verify the formation of the in-situ CEI film, as shown in the attached figure. Figure 4 As shown, after one cycle, the manganese dioxide positive electrode exhibits OH and CO bonds, indicating the accumulation of organic matter on the manganese dioxide surface, i.e., the formation of CEI. Furthermore, based on the existing OH and CO bonds, -COO and CH bonds appear after 50 cycles, indicating the continuous formation process of the CEI film.
[0049] Example 2
[0050] 1) Preparation of the electrolyte for Example 2 (volume ratio of DOP:precursor solution = 1 / 2): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 25 mL of dioctyl phthalate was added to solution B, stirred for 1 hour, and sonicated for 0.3 hours to obtain the electrolyte for Example 2.
[0051] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0052] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of the soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (area 84 cm²) prepared in Example 2 are used. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Example 2), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 5 As shown, a 75% capacity retention rate is achieved after 70 cycles (capacity retention rate = capacity at 70th cycle / maximum capacity within 70 cycles).
[0053] Example 3
[0054] 1) Preparation of the electrolyte of Example 3 (volume ratio of DOP:precursor solution = 1 / 4): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 12.5 mL of dioctyl phthalate was added to solution B, stirred for 1 hour, and sonicated for 0.3 hours to obtain the electrolyte of Example 3.
[0055] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0056] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of the soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (area 84 cm²) prepared in Example 3 are used. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Example 3), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 6 As shown, a capacity retention rate of 68% was achieved after 70 cycles (capacity retention rate = capacity at 70th cycle / maximum capacity within 70 cycles), indicating that although a decrease in the DOP concentration ratio can still have a certain effect, the performance is not as good as in Example 1.
[0057] Example 4
[0058] 1) Preparation of the electrolyte of Example 4 (volume ratio of DOP:precursor solution = 1 / 5): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 10 mL of dioctyl phthalate was added to solution B, stirred for 1 hour, and sonicated for 0.3 hours to obtain the electrolyte of Example 4.
[0059] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0060] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of the soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (area 84 cm²) prepared in Example 4 are used. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Example 4), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2The pouch cell was tested at a current density as shown in the attached figure. Figure 7 As shown, a 66% capacity retention rate was achieved after 70 cycles (capacity retention rate = capacity at cycle 70 / maximum capacity within 70 cycles). Compared to Example 3, the continuous decrease in DOP concentration led to a continuous weakening of the effect, and the performance was further reduced than in Example 3. This indicates that when DOP:precursor solution = 1 / 3, the effect is better than that of DOP:precursor solution.
[0061] =1 / x (x>3) brings better results.
[0062] Example 5
[0063] 1) Preparation of the electrolyte in Example 5 (i.e., DOP electrolyte): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contains 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 16.7 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain the DOP electrolyte.
[0064] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 20 cm². 2 The loading capacity is 10 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0065] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain a sheet with an area of 20 cm². 2 4) Preparation of the soft-pack battery: The DOP electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (20 cm² area) prepared above are combined. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, the separator (with DOP electrolyte added), and the zinc negative electrode in that order, then placing them in a heat-shrink film and heating it to ensure that the heat-shrink film adheres tightly to and fixes the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery.
[0066] 5) Testing of the pouch battery: The pouch battery was combined with a 3V / 400mA solar panel. The solar panel converted solar energy into electrical energy, which was then stored in the pouch battery. The battery was then discharged at different current densities using a blue-light system (see attached diagram). Figure 8 As can be seen from the figure, this pouch cell can meet the discharge test requirements of photovoltaic energy storage under different current densities.
[0067] Example 6
[0068] 1) Preparation of the electrolyte (DOP electrolyte) in Example 6: 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain a clear solution B. Finally, 16.7 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain the DOP electrolyte.
[0069] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 20 cm². 2 The loading capacity is 20 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0070] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain a sheet with an area of 20 cm². 2 4) Preparation of the soft-pack battery: The DOP electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (20 cm² area) prepared above are combined. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, the separator (with DOP electrolyte added), and the zinc negative electrode in that order, then placing them in a heat-shrink film and heating it to ensure that the heat-shrink film adheres tightly to and fixes the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery.
[0071] 5) Testing of the pouch battery: The pouch battery was combined with a 6V / 3A solar panel, charged using solar energy, and subjected to long-cycle discharge through a blue-electric system to verify the long-term stability of the system when applied to photovoltaic energy storage (see appendix). Figure 9 As shown in the figure, this pouch battery demonstrates long-term energy storage stability. It maintained relatively stable capacity performance throughout 30 cycles, meeting the requirement of approximately 3.5 mAh / cm³. 2 The surface capacity.
[0072] Comparative Example 1
[0073] 1) Preparation of Comparative Example 1 electrolyte (i.e., precursor solution, volume ratio DOP:precursor solution = 0): 50 mL of deionized water was added to a mixture of 16.145 g zinc sulfate and 1.5099 g manganese sulfate to obtain solution A of 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain Comparative Example 1 electrolyte.
[0074] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0075] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in Comparative Example 1. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 1), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain a soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 2 As shown in Comparative Example 1, only 27% of the capacity was retained after 70 cycles (capacity retention = capacity at 70th cycle / highest capacity within 70 cycles), which demonstrates that DOP electrolyte has a strong advantage in improving the electrochemical performance of zinc / manganese dioxide battery systems.
[0076] 6) Positive electrode characterization: The manganese dioxide positive electrode after cycling was characterized to demonstrate that no CEI formed on the surface of manganese dioxide in the electrolyte of Comparative Example 1, as shown in the attached figure. Figure 4 As shown. Compared to the DOP electrolyte, no other products appeared on the surface of the manganese dioxide cathode after cycling with the comparative electrolyte, indicating that CEI does not form in situ during the cycling of the comparative electrolyte (i.e., the precursor solution), and its formation is due to the beneficial effect brought about by the introduction of DOP.
[0077] Comparative Example 2:
[0078] 1) Preparation of Comparative Example 2 electrolyte (volume ratio of DOP:precursor solution = 3 / 1): 5 mL of deionized water was added to a mixture of 1.6145 g zinc sulfate and 0.15099 g manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain solution B. Finally, 15 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain comparative example 2 electrolyte.
[0079] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0080] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in the preparation of Comparative Example 2. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 2), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain the soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 10 As shown, it was found to be related to the attached Figure 3 The time-voltage / current graph of Example 1 is completely different, and the basic charge and discharge are completed instantly. This is because the high DOP concentration makes it impossible for it to carry out a normal charge and discharge process (basically in an open circuit state), indicating that the electrolyte at this comparative concentration ratio cannot meet the battery's operating requirements.
[0081] Comparative Example 3:
[0082] 1) Preparation of Comparative Example 3 electrolyte (volume ratio of DOP:precursor solution = 2 / 1): 5 mL of deionized water was added to a mixture of 1.6145 g zinc sulfate and 0.15099 g manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain solution B. Finally, 10 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain comparative example 3 electrolyte.
[0083] 2) Preparation of manganese dioxide positive electrode sheet: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0084] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in the preparation of Comparative Example 3. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 3), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain the soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 11 As shown, it was found to be related to the attached Figure 3 The time-voltage / current graph of Example 1 is completely different, and the basic charge and discharge are completed instantly. This is because the high DOP concentration makes it impossible for it to carry out a normal charge and discharge process (basically in an open circuit state), indicating that the electrolyte at this comparative concentration ratio cannot meet the battery's operating requirements.
[0085] Comparative Example 4:
[0086] 1) Preparation of Comparative Example 4 electrolyte (volume ratio of DOP:precursor solution = 1 / 1): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain solution B. Finally, 50 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain comparative example 4 electrolyte.
[0087] 2) Preparation of manganese dioxide positive electrode: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0088] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in the preparation of Comparative Example 4. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 4), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain the soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 12 As shown, it was found to be related to the attached Figure 3 The time-voltage / current graph of Example 1 is completely different, and the basic charge and discharge are completed instantly. This is because the high DOP concentration makes it impossible for it to carry out a normal charge and discharge process (basically in an open circuit state), indicating that the electrolyte at this comparative concentration ratio cannot meet the battery's operating requirements.
[0089] 6) Cause Investigation: To confirm the cause of the malfunction, electrochemical impedance spectroscopy was performed on Comparative Example 4 and Example 1, and the battery impedance was calculated for each. The results are shown in the appendix. Figure 13As shown in the figure, compared to Example 1, Comparative Example 4 exhibits a larger electrochemical impedance arc, indicating higher battery impedance, which is detrimental to normal battery operation. This demonstrates that a higher DOP concentration leads to increased battery impedance, resulting in the battery's inability to charge and discharge normally. In Example 2, a DOP:precursor solution ratio of 1:2 allows DOP to function effectively, while in Comparative Example 4, a DOP:precursor solution ratio of 1:1 fails to achieve the desired effect, or even prevents normal operation. This indicates that a higher DOP:precursor solution ratio of 1:1...
[0090] When 1 / y (y≤1), the introduction of DOP is detrimental and will cause the battery to be in an open circuit state.
[0091] Comparative Example 5:
[0092] 1) Preparation of Comparative Example 5 electrolyte (volume ratio of DOP:precursor solution = 1 / 6): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain solution B. Finally, 8.3 mL of dioctyl phthalate was introduced into solution B, and the mixture was stirred for 1 hour and sonicated for 0.3 hours to obtain comparative example 5 electrolyte.
[0093] 2) Preparation of manganese dioxide positive electrode: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0094] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in the preparation of Comparative Example 5. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 5), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain the soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 14 As shown, after 70 cycles, the capacity retention rate was only 41% (capacity retention rate = capacity at 70th cycle / maximum capacity within 70 cycles), which is much lower than the level of Example 1, but still higher than Comparative Example 1, indicating that a small amount of DOP additive can still have a certain effect.
[0095] Comparative Example 6:
[0096] 1) Preparation of Comparative Example 5 electrolyte (volume ratio of polysorbate:precursor solution = 1 / 3): 50 mL of deionized water was added to a mixture of 16.145 g of zinc sulfate and 1.5099 g of manganese sulfate to obtain solution A, which contained 2 mol / L zinc sulfate and 0.2 mol / L manganese sulfate. Further, solution A was stirred for 1 hour and sonicated for 0.3 hours to obtain solution B. Finally, 16.7 mL of polysorbate was introduced into solution B, stirred for 1 hour, and sonicated for 0.3 hours to obtain comparative example 6 electrolyte.
[0097] 2) Preparation of manganese dioxide positive electrode: Commercial manganese dioxide (MnO2), conductive agent Super P, and binder PVDF were mixed evenly at a mass ratio of 7:2:1, and an appropriate amount of dispersant NMP was added to prepare a manganese dioxide positive electrode slurry of a certain viscosity. This slurry was then coated onto a graphite felt current collector with an area of 84 cm². 2 The loading capacity is 50 mg / cm³. 2 After drying at 80°C under vacuum for 24 hours, manganese dioxide positive electrode sheets were obtained.
[0098] 3) Preparation of zinc negative electrode sheet: Commercial zinc foil was cut to obtain an area of 84 cm². 2 4) Preparation of a soft-pack battery: The electrolyte, manganese dioxide positive electrode, zinc negative electrode, and Whatman GF / A glass fiber separator (with an area of 84 cm²) prepared above are used in the preparation of Comparative Example 6. 2 Heat shrink film and aluminum-plastic film are applied. Figure 1 The assembly process involves stacking the manganese dioxide positive electrode, separator (with electrolyte added as in Comparative Example 6), and zinc negative electrode in that order, then placing them in heat-shrink film and heating it to ensure a tight fit between the heat-shrink film and the battery cell. Finally, it is sealed in an aluminum-plastic film to obtain the soft-pack battery. 5) Testing of the soft-pack battery: Using the Blue Electric system, at 10 mA / cm... 2 The pouch cell was tested at a current density as shown in the attached figure. Figure 15 As shown, after 70 cycles, the capacity retention rate was only 11% (capacity retention rate = capacity at 70th cycle / highest capacity within 70 cycles), which is far lower than that of Example 1 and even worse than Comparative Example 1, further demonstrating the superiority of the dioctyl phthalate additive in this invention.
[0099] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.
Claims
1. A dioctyl phthalate electrolyte for aqueous zinc-ion batteries, characterized in that, The electrolyte consists of a mixed aqueous solution of zinc sulfate and manganese sulfate and dioctyl phthalate. The concentrations of each component in the mixed aqueous solution of zinc sulfate and manganese sulfate are 0.5 ~ 3 mol / L for zinc sulfate and 0.01 ~ 1 mol / L for manganese sulfate. The volume ratio of dioctyl phthalate to the mixed aqueous solution of zinc sulfate and manganese sulfate is 1 / 2 ~ 1 / 5.
2. The dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to claim 1, characterized in that, The concentrations of each component in the mixed aqueous solution of zinc sulfate and manganese sulfate are as follows: zinc sulfate 2 mol / L, manganese sulfate 0.2 mol / L.
3. A dioctyl phthalate electrolyte for an aqueous zinc-ion battery according to claim 1 or 2, characterized in that, The volume ratio of dioctyl phthalate to a mixed aqueous solution of zinc sulfate and manganese sulfate is 1 / 3.
4. A method for preparing dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to any one of claims 1 to 3, characterized in that, Includes the following steps: 1) Deionized water is added to a mixture of zinc sulfate and manganese sulfate to obtain solution A; 2) After stirring and dispersing solution A and ultrasonicating it to obtain a homogeneous and clear solution B, i.e., the precursor solution; 3) Add dioctyl phthalate to solution B, stir and disperse, and sonicate to obtain a homogeneous and clear solution C. Solution C is the dioctyl phthalate electrolyte.
5. The method for preparing dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to claim 4, characterized in that, The stirring time in step 2) is 1 hour or more, the ultrasonic time is 0.3 hours or more, and the operating temperature is 25℃ ~ 35℃.
6. The method for preparing dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to claim 4 or 5, characterized in that, The stirring time in step 3) is 1 hour or more, the ultrasonic time is 0.3 hours or more, and the operating temperature is 25℃ ~ 35℃.
7. The application of a dioctyl phthalate electrolyte for an aqueous zinc-ion battery according to any one of claims 1 to 3 in an aqueous zinc-ion battery.
8. The application of the dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to claim 7 in aqueous zinc-ion batteries, characterized in that, A soft-pack battery was prepared by adding dioctyl phthalate electrolyte into a glass fiber separator and combining it with a zinc negative electrode, a manganese dioxide positive electrode, a heat shrink film, and an aluminum-plastic film.
9. A soft-pack battery obtained by applying the dioctyl phthalate electrolyte for aqueous zinc-ion batteries according to claim 7 in an aqueous zinc-ion battery.
10. An application of the pouch cell according to claim 9 in the field of photovoltaic energy storage.
Citation Information
Patent Citations
High-voltage electrolyte and lithium ion battery containing same
CN114914540A
Interface phase of manganese dioxide electrode of aqueous zinc battery and preparation method of interface phase
CN115911248A
Rechargeable aqueous zinc-manganese battery and assembling method thereof
CN114300669A
Alkaline zinc-manganese battery negative electrode and preparation method thereof
CN115084454A